THE EFFECT OF COMIC STRIPS ON STUDENTS’ WRITING SKILL IN NARRATIVE TEXT - Veren Widya; Ashari P. Swondo (Journal MELT (Medium for English Language Teaching), 2021)
The objective of this study was to find out the effect of Comic Strips on Students’ Writing Skill in Narrative Text. The writer used experimental research. The population of this study was all the eleventh grade students of SMKS Sinar Husni 1 BM. The sample was two classes, namely XI-AP.1 and XI-AP.2. The researcher used pre-test and post-test as the research instrument. The technique used in collecting the data was quantitative data t-test. The result of the study showed that the application of comic strips had effect in teaching writing of narrative text. The experimental class got a mean post-test score of 72.97. Meanwhile, the control class got a mean post-test score of 68.74. Furthermore, based on the statistical calculation with the significance level of 5% and 1%, it showed that tobs was higher than ttable that was 2.00 < 4.07 > 2.66. To conclude, it proved that the alternative hypothesis (Ha) was accepted, which stated that there was a significant effect of Comic Strips on Students’ Writing Skill in Narrative Text at the eleventh grade students of SMKS Sinar Husni 1 BM.